Thermal energy accumulation in stratified hot water stores - Cohen, R. R. (Cranfield University, 1986)
Hot water thermal energy stores have the potential to improve and extend the performance of many kinds of energy system. Waperature stratification in the store is likely to affect the system's efficiency. A basic but accurate computer model of the hot water store under various inlet flow conditions is a requisite means of assesiing promising applications of hot water storage by system computer simulation techniques. A microprocessor-controlled test facility has been constructed to evaluate the performance of a 3m 3 hot water store under a wide range of inlet flow conditions, using a temperature step input approach. Three types of inlet/outlet ports have been examined: horizontal, vertical and distributors. The results show that two distinct regions evolve within the store: a fully-mixed region adjacent to the inlet port and a region of smooth 'plug-flow' in the remaining volume of the store. The performance of the store is shown to be defined by the initial depth of the fully-mixed region which in turn is seen to be closely related to the buoyancy and momentum fluxes of the inlet flow. The behAviour of the store and the evident correlations have enabled a one-dimensional computer model of the store to be developed, taking into account the turbulent mixing, vertical heat conduction and heat losses to the surrounding areas. The model has been successfully validated against the results from the step input experiments. The model has been integrated into a computer simulated central heating system which incorporates a hot water store. Predictions have been made, using the simulation, of the energy savings which may be achieved with the use of storage in comparison to a conventional system, and an assessment has been made of the economic viability of the application.